A phase 1/2 trial to assess safety and efficacy of a vaporized 5-methoxy-N,N-dimethyltryptamine formulation (GH001) in patients with treatment-resistant depression - Reckweg, Johannes T.; van Leeuwen, Cees J.; Henquet, Cécile; van Amelsvoort, Therese; Theunissen, Eef L.; Mason, Natasha L.; Paci, Riccardo; Terwey, Theis H.; Ramaekers, Johannes G. (Frontiers in Psychiatry, 2023)
Background: Treatment-resistant depression (TRD) is a substantial public health burden, but current treatments have limited effectiveness. The aim was to investigate the safety and potential antidepressant effects of the serotonergic psychedelic drug 5-MeO-DMT in a vaporized formulation (GH001) in adult patients with TRD. Methods: The Phase 1 part (n=8) of the trial investigated two single dose levels of GH001 (12 mg, 18 mg) with a primary endpoint of safety, and the Phase 2 part (n=8) investigated an individualized dosing regimen (IDR) with up to three increasing doses of GH001 (6 mg, 12 mg and 18 mg) within a single day, with a primary endpoint of efficacy, as assessed by the proportion of patients in remission (MADRS ≤10) on day 7. Results: Administration of GH001 via inhalation was well tolerated. The proportion of patients in remission (MADRS ≤10) at day 7 was 2/4 (50%) and 1/4 (25%) in the 12 mg and 18 mg groups of Phase 1, respectively, and 7/8 (87.5%) in the IDR group of Phase 2, meeting its primary endpoint (p<0.0001). All remissions were observed from day 1, with 6/10 remissions observed from 2 hours. The mean MADRS change from baseline to day 7 was -21.0 (-65%) and -12.5 (-40%) for the 12 and 18 mg groups, respectively, and 24.4 (-76%) for the IDR. Conclusions: Administration of GH001 to a cohort of 16 patients with TRD was well tolerated and provided potent and ultra-rapid antidepressant effects. Individualized dosing with up to three doses of GH001 on a single day was superior to single dose administration.